Analisis Pengoptimalan Supply Chain dan Value Chain di Bulog Kantor Cabang Surabaya Utara - Fadmala, Yuyun; Hayati, Cucu; Hanifah, Hanifah (PUTRA JAWA PUBLISHER, 2024)
The food industry plays a crucial role in meeting the basic human needs for food. To ensure a stable, safe, and high-quality food supply, effective supply chain management in the food industry is essential. This research utilizes a case study approach, focusing on the North Surabaya branch office of BULOG using descriptive analysis methods. Data collected for this study will include primary data through interviews and secondary data obtained from relevant previous research. The importance of efficiency and effectiveness in the supply chain is the goal of analyzing and optimizing the supply chain and value chain of the North Surabaya branch office of BULOG. The value chain involves adding value through various activities such as processing, packaging, and marketing. This research emphasizes the significant role played by Perum BULOG Divre North Surabaya in the context of the food industry, which is also part of Perum BULOG. As a Logistics Agency, it is responsible for the distribution activities and the process of distributing staple food in Indonesia.